2018
DOI: 10.1186/s12864-018-5242-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between latex metabolism gene expression with rubber yield and related traits in Hevea brasiliensis

Abstract: BackgroundExpression patterns of many laticifer-specific gens are closely correlative with rubber yield of Hevea brasiliensis (para rubber tree). To unveil the mechanisms underlying the rubber yield, transcript levels of nine major latex metabolism-related genes, i.e., HMG-CoA synthase (HMGS), HMG-CoA reductase (HMGR), diphosphomevalonate decarboxylase (PMD), farnesyl diphosphate synthase (FPS), cis-prenyltransferase (CPT), rubber elongation factor (REF), small rubber particle protein (SRPP), dihydroxyacid deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…For Matricaria recutita L., MrFPS is most highly expressed in flowers and stems [ 43 ]. In H. brasiliensis , HbFPS is not expressed in roots, stems, leaves, and other tissues but is highly expressed in latex [ 44 ]. These studies have shown that the spatiotemporal expression patterns of ZbDXS and ZbFPS genes in different plants are quite different.…”
Section: Discussionmentioning
confidence: 99%
“…For Matricaria recutita L., MrFPS is most highly expressed in flowers and stems [ 43 ]. In H. brasiliensis , HbFPS is not expressed in roots, stems, leaves, and other tissues but is highly expressed in latex [ 44 ]. These studies have shown that the spatiotemporal expression patterns of ZbDXS and ZbFPS genes in different plants are quite different.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the proteins they encode, genes expressed in the latex of Hevea can be categorized into three groups: defence‐related proteins such as hevein (Broekaert et al, 1990), chitinase (Martin, 1991), b‐1,3‐glucanase (Chye & Cheung, 1995) and HEVER (Sivasubramaniam et al, 1995); rubber biosynthesis‐related proteins such as REF (Goyvaerts et al, 1991), hydroxymethylglutaryl‐CoA reductase, farnesyl diphosphate synthase (Adiwilaga & Kush, 1996), HMG‐CoA synthase (HMGS), diphosphomevalonate decarboxylase (PMD), cis ‐prenyltransferase (CPT), small rubber particle protein (SRPP), dihydroxy acid dehydratase (DHAD) and actin‐depolymerizing factor (ADF) (Wu et al, 2018). latex allergens (proteins) like Hev b 3 (Yeang et al, 1996), Hev b 4, Hev b 5 (Akasawa et al, 1996; Slater et al, 1996) and Hev b 7 (Sowka et al, 1998).…”
Section: Genes/proteins Involved In Rubber Biosynthesismentioning
confidence: 99%
“…• rubber biosynthesis-related proteins such as REF (Goyvaerts et al, 1991), hydroxymethylglutaryl-CoA reductase, farnesyl diphosphate synthase (Adiwilaga & Kush, 1996), HMG-CoA synthase (HMGS), diphosphomevalonate decarboxylase (PMD), cisprenyltransferase (CPT), small rubber particle protein (SRPP), dihydroxy acid dehydratase (DHAD) and actin-depolymerizing factor (ADF) (Wu et al, 2018).…”
Section: Genes/proteins Involved In Rubber Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…is a deciduous perennial species native to the Amazon rainforest and belongs to the Euphorbiaceae family [1]. Latex is extracted from this crop and is the main source of natural rubber for the tire industry, representing up to 90% of the rubber sold in international markets [2]. In Colombia, there are about 69,000 ha of rubber, with an estimated national production of 7500 tons per year, distributed mainly in the states of Meta, Santander, Antioquia, Vichada and Caquetá [3].…”
Section: Introductionmentioning
confidence: 99%